The Effectiveness of Quizizz Media to Increase Appreciation of Pantun Texts in Junior High Schools - Susilo, Jimat; Muliawati, Hesti; Nanda, Ajy Setya; Nurhaniah, Syeisa Annisa (Universitas Pendidikan Mandalika, 2024)
Teachers have not been widely using quiz media in learning. Meanwhile, students urgently need innovative media to stimulate their motivation to learn. This study aims to describe the effectiveness of Quizizz media in improving the ability to appreciate rhyme texts in junior high school students. The research method through classroom action consists of two cycles. Data was collected through observation and student ability tests. The subject of the study was a student of SMPN 1 Kedawung, Cirebon. The research instrument was essay test results in the form of appreciation of the text of rhymes assisted by Quizizz media and the results of observation during learning. Learning outcomes in Cycle I showed that students' average scores and completion percentages remained low, with only 15 (or 45%) able to achieve completion, while 18 (or 54%) did not. In the second cycle, out of 33 students, 22 (67%) achieved completion, and only 16 (48%) did not achieve it. The average score of cycle II increased to 72, with more than 67% of students achieving completion. Based on the results of data analysis, it was shown that quiz media could improve the ability to appreciate rhyme texts in junior high school students.